2010
DOI: 10.1128/jcm.00240-10
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type MIC Distributions for Aminoglycoside and Cyclic Polypeptide Antibiotics Used for Treatment of Mycobacterium tuberculosis Infections

Abstract: The aminoglycosides and cyclic polypeptides are essential drugs in the treatment of multidrug-resistant tuberculosis, underscoring the need for accurate and reproducible drug susceptibility testing (DST). The epidemiological cutoff value (ECOFF) separating wild-type susceptible strains from non-wild-type strains is an important but rarely used tool for indicating susceptibility breakpoints against Mycobacterium tuberculosis. In this study, we established wild-type MIC distributions on Middlebrook 7H10 medium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 18 publications
7
38
0
Order By: Relevance
“…The critical concentrations on 7H10 for KAN, AMK, and CAP were 5.0, 4.0, and 4.0 mg/liter, respectively (33). The MICs of H37Rv ATCC 27294 were 1 mg/liter for each drug, concordant with data from Juréen et al (41). c Resistance-associated genes of isolates cultured in tubes with antibiotics were sequenced.…”
Section: Resultssupporting
confidence: 63%
“…The critical concentrations on 7H10 for KAN, AMK, and CAP were 5.0, 4.0, and 4.0 mg/liter, respectively (33). The MICs of H37Rv ATCC 27294 were 1 mg/liter for each drug, concordant with data from Juréen et al (41). c Resistance-associated genes of isolates cultured in tubes with antibiotics were sequenced.…”
Section: Resultssupporting
confidence: 63%
“…One possible explanation for the observed lack of specificity for predicting phenotypic CAP resistance may lie in the WHO-recommended critical concentration for MGIT 960 DST that we used for our study. Since the current critical concentration was accepted by the WHO, it has been demonstrated that this critical concentration is substantially higher than the epidemiological cutoff (ECOFF) that separates wild-type M. tuberculosis from those with mutations conferring CAP resistance, which might result in non-wild-type isolates being classified as CAP s (38,39). Interpreted in the context of our findings, it is possible that the WHO-recommended critical concentration we used misclassified CAP-resistant organisms as susceptible, resulting in a reduced specificity of the mutation for predicting phenotypic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar MIC distributions have been reported for the same reference strain between different liquid culture systems, with MIC variability of a 2-fold dilution or less (5). Studies using 7H10 agar or Bactec MGIT 960 and Bactec 460 determined MICs against H37Rv of 0.5 g/ml for ofloxacin, 0.125 g/ml for moxifloxacin, 0.25 g/ml for levofloxacin, 2 g/ml for ethambutol, 0.5 g/ml for amikacin, and 1 to 2 g/ml for both kanamycin and capreomycin (14)(15)(16); all of these values lie within the MIC QC ranges we report for these drugs. For isoniazid, a microdilution method using 7H10 agar or Bactec 460 yielded a MIC range of 0.064 to 0.125 g/ml for H37Rv, which is essentially within the MIC QC range of 0.03 to 0.12 g/ml determined in this study (16).…”
Section: Discussionmentioning
confidence: 99%